The influence of using LMS based e-learning media on Arabic language learning outcomes at Muslim Cendekia Primary School Batu - Amalia, Jessica Noer; Al-latifatuzzahra, Siti Safira; Shofura, Syifa; Wicaksono, Meidias Abror (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2025)
This study aims to evaluate the influence of using E-Learning media based on Learning Management System (LMS) on Arabic learning outcomes of fifth grade students at Muslim Cendekia Primary School Batu. The research method used is quantitative with an experimental approach, where students are divided into a control group and an experimental group. The experimental group used LMS-based E-Learning media in the learning process, while the control group used conventional learning methods. Learning outcome data was collected through pre-treatment tests and post-treatment tests. Data analysis showed that there was a significant effect of using LMS based E-Learning media on students' Arabic learning outcomes. The statistical test results prove that the alternative hypothesis (Ha) is accepted and the null hypothesis (Ho) is rejected, with the percentage of the variable use of Arabic learning modules on student learning outcomes amounting to 20.8%. This finding indicates that the implementation of LMS-based E-Learning media can significantly improve Arabic learning outcomes and can be one of the effective solutions in improving the quality of Arabic learning in elementary schools.